2016
DOI: 10.1016/j.ssmph.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly in the education–health gradient: Biomarker profiles among adults with subbaccalaureate attainment levels

Abstract: This Short Communication builds on recent findings that documented an anomaly in the education-health gradient: adults who attended college but did not earn a BA (the subbaccalaureate group) reported an equal or higher level of health problems than adults with high school (HS) diploma. Our aim is to test whether this anomaly holds when we eliminate potential reporting differences, by examining biomarker levels in the subbaccalaureate vs HS groups.Using the restricted 1999–2012 NHANES, we estimate models of bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…We also find reduced risk for Unhealthy behavior clustering among men with “some college,” but not among women. This finding is consistent with previous research that documents an anomaly in the education-health gradient, given that individuals with “some college” gain little in terms of health as compared to their high school graduates (Zajacova and Johnson-Lawrence 2016). Future research, therefore, should consider gender differences in these patterns.…”
Section: Discussionsupporting
confidence: 92%
“…We also find reduced risk for Unhealthy behavior clustering among men with “some college,” but not among women. This finding is consistent with previous research that documents an anomaly in the education-health gradient, given that individuals with “some college” gain little in terms of health as compared to their high school graduates (Zajacova and Johnson-Lawrence 2016). Future research, therefore, should consider gender differences in these patterns.…”
Section: Discussionsupporting
confidence: 92%
“…Previous research has shown that health disparities remain at all SES levels suggesting that education is not a real equalizer. 36,37 For example, as shown by the work by Zajacova et al 36,37 and others, [38][39][40] education does not similarly improve the health of Blacks and Whites. We have shown that this is always the case for almost all outcomes.…”
Section: Discussionmentioning
confidence: 95%
“…This study documented MDRs of educational attainment on Black women’s exercise frequency, which is in support of the MDRs theory (1, 2). In the US, education is not “the great equalizer” (27, 28). As shown by Zajacova, education better promotes the health of Whites than Blacks (27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…In the US, education is not “the great equalizer” (27, 28). As shown by Zajacova, education better promotes the health of Whites than Blacks (27, 28).…”
Section: Discussionmentioning
confidence: 99%